Solid oxide fuel cell anode surface modification by magnetron sputtering of NiO/YSZ thin film - Soloviev A. A. Andrey Aleksandrovich; Shipilova A. V. Anna Viktorovna; Ionov I. V. Igor Vyacheslavovich; Smolyanskiy (Smolyansky, Smolyanskii) E. A. Egor Aleksandrovich; Lauk A. L. Aleksandr Lukyanovich; Kovalchuk A. N. Anastasia Nikolaevna; Remnev G. E. Gennady Efimovich; Lebedinsky A. M. Aleksey Mikhaylovich (Modification of materials with particle beams and plasma flows, 2017)
Title screen